Effects of Increasing Mangrove Bioethanol Content on Exhaust Gas Temperature and Exhaust Emission Characteristics of a Spark-Ignition Engine - Syarifudin Syarifudin; Eflita Yohana; Muchamad Muchamad; Suhartana Suhartana; Firman Lukman Sanjaya; Faqih Fatkhurrozak; Mukhamad Khumaisi Usman (Infotekmesin, 2026)
Green Gasoline Mangrove was produced by blending gasoline with 5%, 10%, and 15% (v/v) mangrove bioethanol. Owing to its higher Research Octane Number (RON) and oxygen content than neat gasoline (G100), this fuel has the potential to improve combustion quality while producing cleaner exhaust emissions. This study aimed to investigate the effects of Green Gasoline Mangrove on the exhaust emission characteristics of a spark-ignition engine. Experimental tests were conducted using a spark-ignition engine mounted on an engine test bench under stationary operating conditions, while exhaust emissions were measured using an integrated gas analyzer. The results showed that increasing the bioethanol concentration was associated with higher NOx emissions and lower CO and HC emissions, accompanied by an increase in Exhaust Gas Temperature (EGT), indicating more complete combustion. At an engine speed of 5000 rpm, NOx emissions were 6.54%, 8.65%, and 11.81% higher for GM5, GM10, and GM15, respectively, whereas CO and HC emissions consistently decreased with increasing bioethanol content. In addition, EGT increased from 337°C for GM5 to 377°C for GM15. These findings indicate that Green Gasoline Mangrove enhances combustion characteristics and reduces CO and HC emissions; however, these improvements are accompanied by an increase in NOx emissions due to the higher combustion temperature.